2022
DOI: 10.3390/nu14153053
|View full text |Cite
|
Sign up to set email alerts
|

KYMASIN UP Natural Product Inhibits Osteoclastogenesis and Improves Osteoblast Activity by Modulating Src and p38 MAPK

Abstract: The imbalance in osteoblast (OB)-dependent bone formation in favor of osteoclast (OC)-dependent bone resorption is the main cause of loss of tissue mineral mass during bone remodeling leading to osteoporosis conditions. Thus, the suppression of OC activity together with the improvement in the OB activity has been proposed as an effective therapy for maintaining bone mass during aging. We tested the new dietary product, KYMASIN UP containing standardized Withania somnifera, Silybum marianum and Trigonella foenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Afterward, a battery of synergistic genes is upregulated by NFATc1 activation, covering Mmp9, Atp6v0d2, Acp5, Dcstamp, and CTSK, which promotes the formation of mature osteoclasts and bone resorption (34,35,57). When osteoclasts perform a resorption function, MMP-9 is indispensable for the migration and resorption function of mature osteoclasts (9,34,46). While Atp6v0d2 not only regulates H + secretion but also dissolves the crystalline hydroxyapatite and organic matrix (34,62,63).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Afterward, a battery of synergistic genes is upregulated by NFATc1 activation, covering Mmp9, Atp6v0d2, Acp5, Dcstamp, and CTSK, which promotes the formation of mature osteoclasts and bone resorption (34,35,57). When osteoclasts perform a resorption function, MMP-9 is indispensable for the migration and resorption function of mature osteoclasts (9,34,46). While Atp6v0d2 not only regulates H + secretion but also dissolves the crystalline hydroxyapatite and organic matrix (34,62,63).…”
Section: Discussionmentioning
confidence: 99%
“…The induction of osteoclast differentiation is in connection with the binding of RANK to RANKL (7,10). And then, RANKL/RANK signaling gives rise to the collection of TNF receptor-associated factor 6 (TRAF6) (9), inducing the mobilization of several subsequent pathways, such as mitogen-activated protein kinase (MAPK) and nuclear factor-κB (NF-κB) pathways (11,21), which are classical pathways related to osteoclast differentiation (10). NFATc1, the critical osteoclastogenesis-controlling master transcription factor, is subsequently initiated to express by RANKL (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al found that Thiaplakortone B (TPB, a natural compound derived from the Great Barrier Reef sponge Plakortis lita) blocked multiple upstream pathways of osteoclast differentiation, including MAPK and NF-κB signaling pathways, which in turn inhibited NFATc1 expression and osteoclast formation (Wang et al 2022d ). Salvadori et al discovered that KYMASIN UP, a new dietary product, inhibited osteoclast formation by reducing p38 MAPK activation, resulting in the downregulation of bone fracture markers (Salvadori et al 2022 ). Qiu et al found that neratinib, a small molecule compound, inhibited the expression of osteoclast-specific genes by inhibiting the MAPK pathway, thereby suppressing osteoclast differentiation as well as cartilage degradation and osteoclast formation (Qiu et al 2022 ).…”
Section: The Rankl/rank Signaling Pathway Activates Nfatc1mentioning
confidence: 99%